Blockchain and Wireless Network Security: A Comprehensive Review of Techniques, Challenges, and Future Prospects - Hassan, Abshir; Ketel, Mohammed (Transactions on Engineering and Computing Sciences, 2025)
In the history of digital ecosystems, security has always been and will continue to be a primary issue. Newer fields of study, such as blockchain and wireless networks, continue to confront the difficulties that are exclusive to them despite technological breakthroughs. This article provides an assessment of these two important domains, diving into their relevance and fundamental security methodologies, primary research, unsolved challenges, and prospective future paths. This article covers the key components of blockchain security and emphasizes the importance of wireless network security. A comparative study of the security of blockchain technology and wireless networks elucidates the distinctive qualities, difficulties, and solutions that each one presents. This paper also explores the synergistic integration of AI and blockchain to address the multifaceted security challenges in modern wireless networks.